The Kynurenine Pathway As a Novel Link between Allergy and the Gut Microbiome - Van der Leek, Aaron P.; Yanishevsky, Yarden; Kozyrskyj, Anita L. (Frontiers in Immunology, 2017)
In the past few decades, the Indoleamine 2,3 Dioxygenase (IDO) subset of the kynurenine (KYN) pathway of tryptophan (TRP) metabolism has been the subject of much research in the area of immune tolerance. In this review, we aim to incorporate new findings on this pathway in relation to allergy and the gut microbiome, while providing a comprehensive overview of the pathway itself. Stimulated by interferon-gamma, IDO acts as a tolerogenic, immuno-suppressive enzyme to attenuate allergic responses by the induction of the KYN-IDO pathway, resultant depletion of TRP, and elevation in KYN metabolites. Acting through the aryl hydrocarbon receptor, KYN metabolites cause T-cell anergy and apoptosis, proliferation of Treg and Th17 cells, and deviation of the Th1/Th2 response, although the outcome is highly dependent on the microenvironment. Moreover, new evidence from germ-free mice and human infants shows that gut microbiota and breast milk are key in determining the functioning of the KYN-IDO pathway. As such, we recommend further research on how this pathway may be a critical link between the microbiome and development of allergy.